2006
DOI: 10.1016/j.psychres.2005.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life for patients with schizophrenia in a Japanese psychiatric hospital

Abstract: Providing a good quality of life (QOL) has recently been recognized as a central purpose of health care in psychiatry. In this study, we performed a detailed evaluation of the subjective QOL of schizophrenic inpatients and examined the relationship of QOL to various patient characteristics. This study was conducted on schizophrenic inpatients and nursing staff members in a Japanese private psychiatric hospital. As a result, only depression showed a weak, but significant, relationship with subjective QOL. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
4
11
0
11
Order By: Relevance
“…There are studies consistent with our conclusion and indicating there is no significant correlation between functioning and duration of disorder, age of onset of the disorder in the patients with schizophrenia [49,59,61]. Despite this, studies indicating opposite results were also reported [30,34].…”
Section: Discussionsupporting
confidence: 87%
“…There are studies consistent with our conclusion and indicating there is no significant correlation between functioning and duration of disorder, age of onset of the disorder in the patients with schizophrenia [49,59,61]. Despite this, studies indicating opposite results were also reported [30,34].…”
Section: Discussionsupporting
confidence: 87%
“…QOL of patients with schizophrenia were lower than the general population (Kugo et al . ). In the current study, QOL domains of patients with schizophrenia were found to be lower than the general population.…”
Section: Discussionmentioning
confidence: 97%
“…These results were consistent with most other international studies (Kugo et al . , Aki et al . , Brissos et al .…”
Section: Discussionmentioning
confidence: 99%
“…Como já descrito, na revisão da literatura de Souza e Coutinho (2005), os resultados mostram que os doentes com esquizofrenia enfrentam o estigma da doença, tal como nos mostra o estudo de Sibitz et al, (2009 Eack et al, (2007), Kugo et al, (2006), Narvaez et al, (2008) incidiram num mesmo resultado.…”
Section: Discussionunclassified
“…Mostraram que a sintomatologia depressiva (Kugo et al, 2006;Narvaez et al, 2008) e sintomatologia psiquiátrica (Eack et al, 2007) estão relacionados com uma pior qualidade de vida subjetiva. Sintomas negativos estão relacionados com pior qualidade de vida objetiva (Narvaez et al, 2008) e uma pior qualidade de vida relaciona-se com ideação suicida (Yan et al, 2013).…”
Section: Methodsunclassified